Combining Ability of Sixteen USA Maize Inbred Lines and Their Outbreeding Prospects in China - Ji-ying Sun; Ju-lin Gao; Xiao-fang Yu; Jian Liu; Zhi-jun Su; Ye Feng; Dong Wang (Agronomy, 2018)
In China, there is an increasing need for greater genetic diversity in maize (Zea mays L.) germplasm and hybrids appropriate for mechanical harvesting. In order to test and distinguish American maize inbred lines with exceptional combining ability, four Chinese maize inbred lines (Chang7-2, Zheng 58, four-144 and four-287) were used to judge the combining ability and heterosis of 16 USA inbred lines by a NCII genetic mating method. The results showed that among the American inbred lines, 6M502A, LH208, NL001, LH212Ht, PHW51, FBLA and LH181 expressed good GCA for yield characteristics; while RS710, PHP76, FBLA, and PHJ89 showed excellent GCA for machine harvesting characteristics. Five hybrids (NL001 × Chang7-2, LH212Ht × Chang7-2, FBLA × four-144, LH181 × four-287, PHK93 × four-287) had better SCA values for yield characteristics, at 1.69, 1.07, 1.48, 1.84 and 1.05, respectively; while NL001 × Chang 7-2, 6M502A × Chang7-2, LH212Ht × Chang7-2, LH181 × four-287, PHW51 × Chang7-2 had better TCA values for yield characteristics, at 3.03, 2.80, 2.41, 2.19 and 1.91, respectively; NL001 × Chang7-2, 6M502A × Chang7-2, LH212Ht × Chang7-2, LH181 × four-287, PHW51 × Chang7-2 showed excellent Control Heterosis values, with 21.48%, 19.64%, 15.93%, 14.05% and 11.60% increases, respectively, compared to the check and potential for future utilization in Inner Mongolian corn production.